2006
DOI: 10.1016/j.avb.2005.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in direct aggression: What are the psychological mediators?

Abstract: NOTICE: this is the author's version of a work that was accepted for publication in Aggression and Violent Behavior. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reected in this document. Changes may have been made to this work since it was submitted for publication. A denitive version was subsequently published in Aggression and Violent Behavior, 11, 3, May-June 2006, 10.1016/j.avb.2005.002. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
107
1
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(127 citation statements)
references
References 269 publications
(251 reference statements)
9
107
1
10
Order By: Relevance
“…Thus, when aggressive cognition is considered, sex differences-at least those regarding the frequency of thoughts about hitting or killing somebody-disappear. Although females try to inhibit their physical aggression (Campbell 2006) and perceive aggression as harmful and dysfunctional due to holding expressive beliefs about aggression (Campbell and Muncer 2008), they maintain physical aggression as the core of the associative network related to aggression concepts, just as men do. However, it remains an open question how it happens that, in spite of activating physically aggressive cognitions, females externalize aggression primarily in indirect ways, as opposed to males, who show consistency with regard to physically aggressive cognitions and behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, when aggressive cognition is considered, sex differences-at least those regarding the frequency of thoughts about hitting or killing somebody-disappear. Although females try to inhibit their physical aggression (Campbell 2006) and perceive aggression as harmful and dysfunctional due to holding expressive beliefs about aggression (Campbell and Muncer 2008), they maintain physical aggression as the core of the associative network related to aggression concepts, just as men do. However, it remains an open question how it happens that, in spite of activating physically aggressive cognitions, females externalize aggression primarily in indirect ways, as opposed to males, who show consistency with regard to physically aggressive cognitions and behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…When typical masculine primes among males are used, their effect on aggressive cognitions should appear mostly in case of physical aggressive cognitions, since physical aggression is typical for males. However, female aggression is guided by the rule of low risk, which means that physical aggression is avoided because retaliation for physical aggression is highly probable and the likelihood of being injured increases (Campbell 2006). Thus, relational and to some extent verbal aggression meets the requirements of so called "effect/danger ratio" (Björkqvist 1994) better than does physical aggression, but little is known about whether this rule also refers to aggressive cognition.…”
Section: The Current Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, we believe that there is no reason to assume that the mechanisms are gender specific. In particular, research has shown that women equally experience anger but tend to control their aggressive behavior more than men (Campbell, 2006;Eagly & Steffen, 1986;Knight et al, 2002). Therefore, it seems plausible that also among females, attribution may affect controllable aggressive behavior more than implicit anger.…”
Section: Limitationsmentioning
confidence: 99%
“…First, aggression research suggests that there are remarkable gender differences in aggressive behavior (Bettencourt & Miller, 1996;Eagly & Steffen, 1986). Because these differences are mainly due to differences in control of aggressive impulses (Campbell, 2006;Knight, Guthrie, Page, & Fabes, 2002) we would have expected complex interactions of gender, attribution, and type of measure. Second, most of previous studies on attribution and aggression that provided the basis for our study were conducted only on male participants (Epstein & Taylor, 1967;Johnson & Rule, 1986;Kremer & Stephens, 1983;Kulik & Brown, 1979;Nickel, 1974;Zillmann & Cantor, 1976).…”
Section: Participantsmentioning
confidence: 99%